PENGARUH LAPORAN KEUANGAN AUDITAN, RESIKO INVESTASI, DAN IMAGE PERUSAHAAN TERHADAP RESPON INVESTOR DALAM PENGAMBILAN KEPUTUSAN INVESTASI (STUDI KASUS PADA PERUSAHAAN INVESTASI DI JEMBER) - Diana Dwi Astuti (RELASI : JURNAL EKONOMI, 2012)
This research aims to know :(1) the influence of audited financial statements, investmen risk, and corporate image simultaneously on the response of investors in making investment decisions, (2) the influence of audited financial statements, investment risk, and the company as a partial image of the responce of investors in making investment decisions. To solve these problems, methods of analysis used were multiple linear regression analysis with the tools SPSS version 13.0 sofware. The results of the analysis : (1) audited financial statements, investment risk, and corporate image simultaneously have significant effect on the response of investors in making investment decisions ; (2) audited financial statements, investment risk, and corporate image partially have significant effect on the response of investors in making investmen decisions.